Sexual Function in Women With Recurrent Pregnancy Loss - Fahimeh Golbabaei; Maryam Gharacheh; Maryam Armand; Soheila Ansaripour; Shima Haghani; Fahimeh Ranjbar (Iran University of Medical Sciences, 2022)
Background: Recurrent pregnancy loss (RPL), as one of the most critical issues in reproductive health, is followed by emotional trauma, social problems, financial concerns, and disruption of marital relations. This study aimed to investigate sexual function in married women with a history of RPL. Methods: This cross-sectional study was conducted on 130 women with a history of RPL who were referred to the recurrent miscarriage clinic of Avicenna Fertility Center in Tehran, Iran, from November 2018 to February 2019. Data were collected using the demographic characteristics form and the female sexual function index (FSFI). Statistical analysis was carried out using SPSS software, version 16. The Kruskal-Wallis and Mann-Whitney tests were used to determine the relationship between the sexual function of the women and their sociodemographic characteristics. The significance level was set at P<0.05. Results: The Mean±SD score of the female sexual function was 26.59±5.73, and 50% of the women had sexual dysfunction (score ≤28). Sexual desire was the most prevalent sexual disorder (72.3%), while vaginal lubrication had the lowest prevalence (5.4%). No relationship was found between the women's sociodemographic characteristics and their sexual function (P<0.05).  Conclusion: The results of this study confirm the need to provide sexual health-related counseling to women who suffer from RPL and refer them to fertility centers